Barking at the Moon: An Editorial Essay - Muntean, Fritz (New Age Movements, Occultism, and Spiritualism Research Library, 2011)
Fritz Muntean provides a historical overview of Contemporary Paganism along with a comparison of funamentalist Wiccans that claim origins of an ancient practice and the Wiccan scholars that refute them. Muntean also explores the broader issue of non-Academics reactions to scholarship and its parallels to Christian Fundamentalism. These 'notes' were originally compiled by Fritz Muntean as part of a larger oral history effort by Violet, The Abysmal Witch and Holly Changer for the Elder Tales on Terra Arcanum. "Experience the memoirs of Fritz Muntean, practitioner of more than 60 years, and teller of extraordinary tales."
Muntean, Fritz. “Barking at the Moon: An Editorial Essay.” April 13, 2011. Fritz Muntean Collection. New Age Movements, Occultism, and Spiritualism Research Library. Valdosta State University. Valdosta, GA. 1 electronic record(s) bag with alternative formats and metadata. 1 object files (.pdf), 22 pages.
Keywords: Wiccan fundamentalism; Wicca--History; Hutton, Ronald--Criticism and interpretation; Hutton, Ronald. Triumph of the Moon; Whitmore, Ben, 1977- Trials of the moon; PantheaCon (2011 : San Jose, Calif.); MerryMeet (1990 : Seattle, Wash.); Kelly, Aidan A. Crafting the art of magic; Essays; Religious materials